Characterization of patients with intestinal invagination at the Hermanos Cordové Hospital in the period 2016-2018 - Guillermo Manuel Figueredo Montero; Suzanne Santiesteban Puerta; Juan David Santaelena Berro; Claudia Amalia Cuevas Rodríguez; Yordan Álvarez Rondón; Jesús Daniel De la Rosa Santana (Universidad de Ciencias Médicas de Granma, 2023)
Introduction: intestinal invagination is the most frequent cause for intestinal obstruction in nursling and little kids; it consists on the slide of part of the intestine into another nearby distal intestine´s portion.  Objective: to characterize patients with intestinal invagination according to epidemiological, analytical, radiological aspects and therapeutic behavior. Method: an observational, descriptive and retrospective study of patients who suffered from intussusception at the Hermanos Cordové Pediatric Hospital, during the period 2016-2018, was carried out. The population was made up of 28 patients, information was collected from medical records and hospital control records. It was processed through the calculation of percentages, arithmetic mean and standard deviation. The following variables were considered: age, sex, complementary tests and therapy. Results: the male sex (71.4%) predominated, which doubled the female sex, and the age group of 7-12 months (46.4%), with a mean age of 8.2 ± 4.7 months. The condition was directly related to risk factors such as Acute Respiratory Infections in 60.7%. The complete blood count was the one indicated for 100% of the infants and within the radiological ones the colon by enema and the simple Rx of the abdomen at 96.4%. Surgical reduction was performed in 64.3% of infants and hydrocolon in 3.6%. Conclusions: it is necessary to perfect the actions aimed at reducing the risk factors that predispose it, it constitutes a surgical emergency, which translates into operative risk and an increase in hospital costs.